Technology Integration in Counseling Services: Development of E-Counseling as a Strategy for Handling Psychological Problems of Junior High School Students - Cempaka Puri; Dwi Yulianti; Herpratiwi Herpratiwi; Rangga Firdaus (Tekno - Pedagogi)
The use of technology-based e-counselling systems has been shown to have a significant impact on improving students' psychological well-being, especially in overcoming problems of academic stress, emotional anxiety, and depression. This study aims to develop and test the effectiveness of an e-counselling system in supporting students' mental health management using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. With a two-group experimental design involving 50 seventh grade students at SMPN 1 Terbanggi Besar, the experimental group was given access to the e-counselling system, while the control group followed conventional counselling services. The results showed that the use of the e-counselling system resulted in a significant decrease in students' psychological symptoms, with the average anxiety score dropping from 6.5 to 2.9, and depression from 5.6 to 2.1. In contrast, the control group showed smaller changes. An independent t-test (t = 57.11; p < 0.05) confirmed that e-counselling was more effective in reducing anxiety and depression, and improving students' emotion regulation skills. In addition, the e-counselling system was shown to provide more flexible, responsive, and safe access to counselling services, with 80% of students feeling more comfortable in disclosing their personal problems through this platform. These findings suggest that technology integration in counselling services can be an innovative solution in improving students' psychological well-being and supporting the creation of an emotionally healthy learning environment.